2012
DOI: 10.1080/1351847x.2012.722117
|View full text |Cite
|
Sign up to set email alerts
|

How value–glamour investors use financial information: UK evidence of investors’ confirmation bias

Abstract: Abstract:The paper investigates investor's behaviour in the context of value-glamour investing and fundamental analysis, and provides a direct test of the confirmation bias by bringing together the evidence from several strands of literature into a well-defined framework of investor behaviour. The empirical evidence presented is in line with a model of investor's asymmetric reaction to good and bad news due to confirmation bias. Pessimistic value investors typically under-react to good financial information, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
4
21
0
Order By: Relevance
“…They found that biased investors choose messages that support their beliefs, exhibiting confirmation bias, and trade more actively. This is also supported by Duong et al (2014), who found confirmation bias among UK investors. Their study concluded that pessimistic value investors tend to overreact to bad information, whereas optimistic value investors overreact to good information.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…They found that biased investors choose messages that support their beliefs, exhibiting confirmation bias, and trade more actively. This is also supported by Duong et al (2014), who found confirmation bias among UK investors. Their study concluded that pessimistic value investors tend to overreact to bad information, whereas optimistic value investors overreact to good information.…”
Section: Introductionsupporting
confidence: 65%
“…Since the past decades, a voluminous literature has been exploring the effect of psychological factors such as overconfidence bias (Gervais & Odean, 2001;Glaser & Weber, 2007;Kourtidis et al, 2017;Odean, 1998), confirmation bias (Duong et al, 2014;Park et al, 2013), self-serving bias (Chin et al, 2018;Moosa & Ramiah, 2017), and behavioural biases such as disposition effect, mental accounting, heuristics bias, herding, etc. on investors' anomaly such as excessive trading volume or trading frequency (Baker et al, 2019;Barber et al, 2009;Barberis & Huang, 2001;Chen et al, 2007;Choe & Eom, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Practitioner-focused strategy writing emphasizes the need for managers to consider the effects of the bias (Schoemaker & Day, 2009;Urbany, Reynolds, & Phillips, 2008). Thus it seems clear that confirmation bias represents a fundamental aspect of how individuals process information, regardless of setting or context (e.g., Duong, Pescetto, & Santamaria, 2014, Minas, Potter, Dennis, Bartelt, & Bae, 2014.…”
Section: The Implications Of Social Psychology and Social Cognition Tmentioning
confidence: 99%
“…People are justifying that the decline in Bitcoin prices is only temporary and will rise again. Duong, Pescetto, & Santamaria (2014) who researched stock trading listing on the UK stock exchange during 1991-2007 found evidence of confirmation bias on stock investors in responding to good and bad information. Park et al (2010) who observed the behaviour of 502 investors in South Korea proved that investors experienced confirmation bias when processing information from message boards.…”
Section: Confirmation Biasmentioning
confidence: 99%